2006
DOI: 10.1590/s1807-59322006000500015
|View full text |Cite
|
Sign up to set email alerts
|

An Anatomical Study of the Subcoracoid Space

Abstract: PURPOSE:To evaluate the amplitude of the subcoracoid space under maximum internal and external rotations of the humeral head and measure the distance between the apex of the coracoid process and the following anatomical structures: (a) point of entry of the musculocutaneous nerve and its branches into the coracobrachial muscles and into the short head of the biceps brachii muscle; (b) acromial artery; (c) lesser tubercle of the humerus. METHOD: Thirty shoulders of fresh cadavers, without any kind of shoulder p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 13 publications
0
14
0
Order By: Relevance
“…Synovitis within the rotator interval is debrided and the coracohumeral interval is examined. If the interval is less than 8mm in females or less than 10mm in males, [ 22 , 23 ] coracoplasty is performed to reestablish the dimensions of the interval by anteriorizing, medializing, and superiorizing the margins of the coracoid with an arthroscopic bur. When coracoplasty is necessary, the subscapularis tendon is critically scrutinized and addressed as indicated, as it is often pathologically involved with a stenotic coracohumeral interval [ 23 ].…”
Section: Surgical Techniquementioning
confidence: 99%
“…Synovitis within the rotator interval is debrided and the coracohumeral interval is examined. If the interval is less than 8mm in females or less than 10mm in males, [ 22 , 23 ] coracoplasty is performed to reestablish the dimensions of the interval by anteriorizing, medializing, and superiorizing the margins of the coracoid with an arthroscopic bur. When coracoplasty is necessary, the subscapularis tendon is critically scrutinized and addressed as indicated, as it is often pathologically involved with a stenotic coracohumeral interval [ 23 ].…”
Section: Surgical Techniquementioning
confidence: 99%
“… 5 , 12 Bhatia et al 2 performed a large-scale anatomic study of 101 human scapulae and found significant differences in several anatomic parameters between male and female specimens. Ferreira Neto et al 5 confirmed these sex-based differences in the subcoracoid space. Specifically, there was a smaller distance between the coracoid apex and the lesser tuberosity in female specimens compared to male specimens.…”
mentioning
confidence: 99%
“…Specifically, there was a smaller distance between the coracoid apex and the lesser tuberosity in female specimens compared to male specimens. 5 Gumina et al 12 also characterized the shape of the coracoglenoid space in 204 scapulae. No study to date has demonstrated an association between age and the anatomy of the coracoid process and the subcoracoid space.…”
mentioning
confidence: 99%
“…Some studies have reported smaller coracohumeral distances in women, 13 , 37 while others reported no differences in coracohumeral distance or incidence of subcoracoid impingement between sexes. 7 , 12 , 34 , 38 While it is unclear whether differences exist between sexes, our data only reflect the male population. Secondly, biplane fluoroscopy and CT imaging do not depict the soft tissue structures within the coracohumeral interval (articular cartilage, articular capsule, subscapularis muscle and tendon, and subcoracoid bursa).…”
Section: Discussionmentioning
confidence: 89%
“…Subcoracoid impingement, while relatively uncommon in clinical incidence when compared to subacromial impingement, has been increasingly diagnosed in patients with anterior shoulder pain and tenderness. 7 9 , 11 , 27 However, studies have suggested that subcoracoid impingement may not be as rare as once thought. 6 , 8 , 12 , 22 , 26 , 33 In fact, one study reported that 19% of patients with combined subscapularis, supraspinatus, and infraspinatus tears had subcoracoid impingement, 26 and another reported subcoracoid impingement as a postoperative complication in 5.1% of patients following rotator cuff repair and anterior acromioplasty.…”
mentioning
confidence: 99%